UMPSA students develop PrEduBuddy smart app to monitor academic performance in real-time - Nur Hartini, Mohd Hatta (UMPSA, 2025)
PEKAN, 25 August 2025 – The research idea for the PrEduBuddy smart app emerged when a group of students from the Centre for Mathematical Sciences (PSM), Universiti Malaysia Pahang Al-Sultan Abdullah (UMPSA), led by Hasnur Nauwirah Hisham, together with Nurin Mastura Jaafar and Husna Syazwana Mohd Sahar, realised that many students faced difficulties calculating carry marks in real-time.